A Fully Reconfigurable Polarimetric Phased Array Antenna Testbed. (6th August 2014) - Perera, Sudantha; Pan, Yu; Zhang, Yan; Yu, Xining; Zrnic, Dusan; Doviak, Richard
Abstract : The configurable phased array demonstrator (CPAD) is a low-cost, reconfigurable, small-scale testbed for the dual-polarized array antenna and radar prototype. It is based on the concept that individual transmit and receive (TR) modules and radiating elements can be configured in different ways to study the impact of various array manifolds on radiation pattern performance. For example, CPAD is configured as (a) a 4 × 4 planar array, (b) a planar array with mirror configuration, and (c) a circular array to support the multifunctional phased array radar (MPAR) system risk reduction studies. System descriptions are given in detail, and measurements are made and results are analyzed.